An Application of the Sonine-Letnikov Fractional Derivative for the Radial Schrodinger Equation - Ozturk, Okkes; Yilmazer, Resat (Mdpi, 2019)
The Sonine-Letnikov fractional derivative provides the generalized Leibniz rule and, some singular differential equations with integer order can be transformed into the fractional differential equations. The solutions of these equations obtained by some transformations have the fractional forms, and these forms can be obtained as the explicit solutions of these singular equations by using the fractional calculus definitions of Riemann-Liouville, Grunwald-Letnikov, Caputo, etc. Explicit solutions of the Schrodinger equation have an important position in quantum mechanics due to the fact that the wave function includes all essential information for the exact definition of a physical system. In this paper, our aim is to obtain fractional solutions of the radial Schrodinger equation which is a singular differential equation with second-order, via the Sonine-Letnikov fractional derivative.
Keywords: fractional calculus; Sonine-Letnikov fractional derivative; generalized Leibniz rule; radial Schrodinger equation